(3CTZGd GdNTH ai YeGFQ HNGQi ai YUQ GdTjHGfjjf NdGd GdbQfjf (B10(3`(B11(3g`(B/16(3`(B17(3e(B/ s - (3SGejI MSf YKeGf MSfs; (3CMeO QLH eMeO Ydi (B: s; (3TGOjI GdOShbi YHOGdYRjR cTc (B: s ((3GdbGgQI (B: s (3SGejI MSf YKeGf MSf (B: s, 2018)
(3h bO bSeJ GdOQGSI Edi ebOeI h JegjO h HGHjf h NGJeI(B: (3Ydi GdfMh GdJGdi(B. (3ebOeI(B: (3h JJVef CgejI GdehVhY h CSHGH GNJjGQg h UYhHGJ GdHMK h GdOQGSGJ GdSGHbI h GdefgL GdeJHY ai GdOQGSI(B. (3JegjO(B: (3h jJVef OQGSI eNJUQI Yf eOjfI HNGQi ef GdfGMjI GdLZQGajI h GdJGQjNjI h GdMVGQjI ai aJQI GdOQGSI(B: (3ceG JVef GdJegjO LRAG Yf JGQjN UfGYI GdCNTGH ai HNGQi(B. (3GdHGH GdChd(B: (3h jJVef OQGSI hUajI h JhKjbG ddCTZGd GdNTHjI eMd GdOQGSI(B: (3h jfbSe Edi SHYI aUhd HMSH GdJQJjH GdRefi dJdc GdCTZGd(B. (3GdHGH GdKGfi(B: (3h jJVef GdOQGSI GdJMdjdjI ddYfGUQ GdRNQajI h GdehGO GdNGe(B: (3h GdCSGdjH GdUfGYjI h GdRNQajI h GdJCKjQGJ GdeNJdaI Ydi GdCTZGd GdNTHjI ai HNGQi ai GdaJQI ehVY GdOQGSI(B: (3h YhGed GfJbGd Jdc GdJCKjQGJ(B: (3h jfbSe Pdc GdHGH Edi CQHYI aUhd gi(B: (3GdaUd GdChd(B: (3h jJVef OQGSI GdeGOI GdNGe h GdeQGcR GdUfGYjI h CfhGY GdCNTGH GdUfGYjI ai HNGQi h GdYhGed GdeDKQI Ydi CTZGd GdNTH ai HNGQi(B. (3GdaUd GdKGfi(B: (3h jJVef OQGSI jJVef GdJCKjQGJ GdafjI GdeNJdaI ShGA cGfJ JCKjQGJ eMdjI Ch CLfHjI (B((3UjfjI (B- (3EjQGfjI (B- (3JQcjI(B): (3h cja SGYOJ GdYhGed GdGbJUGOjI h GdSjGSjI h GdehbY GdLZQGai h GdehQhK Gdafi Ydi GfJbGd Jdc GdJCKjQGJ Edi GdCTZGd GdNTHjI ai GdaJQI ehVY GdOQGSI(B. (3GdaUd GdKGdK(B: (3h jJVef OQGSI GdYfGUQ GdRNQajI (B((3GdRNGQa GdfHGJjI (B- (3GdCTZGd GdgfOSjI (B- (3GdfbhT GdcJGHjI(B): (3h GdJi XgQJ Ydi GdJMa GdNTHjI ehVhY GdOQGSI(B: (3h JJHYgG hGdJWhQ GdPi WQC Ydi CTcGdgG h edGFeJgG ddJMa GdNTHjI ehVhY GdOQGSI GdefaPI YdjgG TcdG h eVehfG(B: (3eUMhHG HCTcGd JhVjMjI dJdc GdRNGQa(B. (3GdaUd GdQGHY(B: (3h jJVef OQGSI ebGQfI Hjf GdCTZGd GdNTHjI ehVhY GdOQGSI h GdCTZGd GdNTHjI GdeYGUQI dgG(B: (3h bO GNJJeJ GdOQGSI HGdNGJeI(B: (3Ke agQS GdCTcGd h GddhMGJ(B: (3Ke bGFeI GdeUGOQ h GdeQGLY(B: (3h CNjQG cJGdhL GddhMGJs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBKGQ (B- (3bSe GdCKGQ GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3BSjG GdhSWis; (3CHhGHs; (3GdCTJQGNGfjjfs